Strengthening pedagogical competence of elementary teachers in the digital era - Asep Ahyar; Yusuf Tri Herlambang (Curricula: Journal of Curriculum Development, 2025)
Digital transformation requires elementary school teachers to have pedagogical competencies that are not only strong in theory but also adaptable to technological developments. This article aims to examine strategies for strengthening the pedagogical competencies of elementary school teachers in the digital age. This study employed a systematic literature review method, comprising four stages of analysis: identification, screening, feasibility testing, and inclusion. Data were collected from various academic sources, including scientific journals, articles, and relevant books, with a focus on literature published between 2020 and 2025. The results of the study indicate that pedagogical competencies in the digital age involve integrating digital literacy, technology-based learning innovations, and collaborative skills. Challenges include infrastructure limitations, low digital literacy, and resistance to change. Effective strategies to address these challenges include continuous training, strengthening professional communities, and institutional policy support. Best practices identified include digital project-based learning, the use of Learning Management Systems (LMS), and the development of online teacher communities. This study emphasizes the importance of collaboration among teachers, schools, and policymakers in developing an innovative and sustainable basic education ecosystem in the digital age.   Abstrak Transformasi digital menuntut guru sekolah dasar memiliki kompetensi pedagogik yang tidak hanya kuat secara teoritis, tetapi juga adaptif terhadap perkembangan teknologi. Artikel ini bertujuan untuk mengkaji strategi penguatan kompetensi pedagogik guru sekolah dasar di era digital. Kajian ini dilakukan melalui metode systematic literature review dengan empat tahapan analisis, yaitu identifikasi, penyaringan, uji kelayakan, dan inklusi. Data dikumpulkan dari berbagai sumber akademik seperti jurnal ilmiah, artikel, dan buku yang relevan, dengan fokus pada literatur terbitan tahun 2020–2025. Hasil kajian menunjukkan bahwa kompetensi pedagogik di era digital melibatkan integrasi literasi digital, inovasi pembelajaran berbasis teknologi, serta keterampilan kolaboratif. Tantangan yang dihadapi meliputi keterbatasan infrastruktur, rendahnya literasi digital, dan resistensi terhadap perubahan. Strategi efektif untuk mengatasinya meliputi pelatihan berkelanjutan, penguatan komunitas profesional, serta dukungan kebijakan institusional. Praktik baik yang ditemukan mencakup pembelajaran berbasis proyek digital, pemanfaatan Learning Management System (LMS), dan pengembangan komunitas guru daring. Studi ini merekomendasikan pentingnya kolaborasi antara guru, sekolah, dan pemangku kebijakan dalam membangun ekosistem pendidikan dasar yang inovatif dan berkelanjutan di era digital. Kata kunci: guru sekolah dasar; kompetensi pedagogik; transformasi digital